Análise sobre o enterramento de infraestrutura de redes dos setores de distribuiç\~ao de energia e telecomunicaç\~oes - Bruna de Abreu Martins; Lucas Gustavo Arango; Luis Claudio Kubota (Instituto de Pesquisa Econômica Aplicada (IPEA), 2022)
– This Discussion Paper analyzes the implementation of underground networks and their impacts on the energy and telecommunications sectors, through the main benefits, lessons learned regarding international benchmarking and an economic-financial analysis. The implementation of underground distribution networks is a reality all over the world and although the sharing of this infrastructure brings mutual benefits to the sectors involved, in Brazil the penetration of this type of grid remains quite low, mainly due to the high investment required. Regarding to the power quality, underground networks improve the system reliability, presenting better values of continuity indicators in relation to those of aerial networks. This improvement causes an economic gain for the electricity companies, reducing the cost of undistributed energy and the compensation paid to consumers due to violations on these indicators limits. Therefore, the current work presents a methodology to quantify the increase in billing for electricity companies due to the implementation of underground networks and compare the economic viability of this type of network in relation to aerial networks. For this, a hypothetical case study in ten different regions in Brazil is conducted in order to show how economic viability varies from region to region. The results showed that for regions with a very high load density and high values of energy interruptions, underground networks are more economically viable than the aerial ones.
Keywords: K23; K32; L94; L96; 330; underground networks; infrastructure sharing; power quality; reliability; undistributed energy